A Study on Smartphone Addiction and Its Behavioral and Health Hazards Among Paramedical Students of Devdaha Medical College and Research Institute - Sharma, S.; Panta, R.; Patel, S.; Mahar, N.; Pandey, N.; Lamsal, S. (Devdaha Medical Journal, 2023)
Introduction: Smartphone with its various functionalities has become an essential part of our daily activities and its use has been increasing. This has sparked concerns about usage and addiction, particularly among students. It is known that poor sleep is very common among medical and paramedical students. Among all factors smart phone has also contributed on deleterious effects on sleep. The main purpose of this study was to know about smart phone addiction and its health hazards among paramedical students of DMCRI. Method: A descriptive cross-sectional study was conducted in first year to final year paramedical students of Devdaha Medical College where the sample size was 119 students. The sample size was purposively selected ensuring all students participation from first year to final year paramedical students. Result: It was found that from 119 students the 48.86 % of the participants were using smart phone more than 5 hrs a day and 76.5% of the participants use their smart phone while studying. Conclusion: The high prevalence of excessive smart phone usage among paramedical students is a cause for concern and is detrimental to their health. The research concerns for the smart phone addiction and its health-related risks. The study recommends increasing self-awareness for help-seeking to regulate smart phone usage and providing counselling services for students.